Synthesis and Application of Tetrafluoroethylene (CF2CF2)-Containing Acetylene Derivatives - Egashira, Gen; Kajimoto, Chihiro; Kataoka, Takuto; Yamada, Shigeyuki; Konno, Tsutomu (Synthesis, 2020)
On treating 1,3,4-tribromo-1,1,2,2-tetrafluorobutane, readily prepared from commercially available 4-bromo-3,3,4,4-tetrafluorobut-1-ene, with 3.3 equivalents of LHMDS at 0 °C in THF, the corresponding lithium acetylide could be prepared quantitatively. The acetylide reacted well with various aldehydes, ketones, or chlorosilanes to give the corresponding acetylene derivatives in high yields. It was also found that various iodoarenes could participate in the cross-coupling reaction with the zinc acetylide, readily prepared from the lithium acetylide and ZnCl2·TMEDA complex, in the presence of Pd(PPh3)4 to bring about the adducts in high yields. Thus-obtained acetylene derivatives underwent smooth Diels–Alder reaction with various 1,3-dienes to afford the corresponding 1,4- or 1,3-cyclohexadiene derivatives. In addition, it was revealed that the oxidative aromatization of the resulting cyclohexadiene derivatives with DDQ took place very smoothly, providing the multi-substituted benzene derivatives having a tetrafluoroethylene group.
Keywords: tetrafluoroethylene; 4-bromo-3,3,4,4-tetrafluorobut-1-ene; 1,3,4-tribromo-1,1,2,2-tetrafluorobutane; acetylene derivatives; Diels–Alder reaction; oxidative aromatization